Design, synthesis, antiproliferative assessments, and computational studies of new quinolin-2(1H)-ones as dual EGFR/HER-2 inhibitors - Al-Wahaibi, Lamya H.; Abou-Zied, Hesham A.; Nieger, Martin; Bräse, Stefan; Youssif, Bahaa G. M.; Tawfik, Hendawy (Frontiers in Chemistry, 2025)
IntroductionA novel series of quinolin‐2(1H)‐one derivative was rationally designed, synthesized, and characterized as potential dual inhibitors of EGFR and HER-2.MethodsStructural elucidation was achieved through IR, NMR, mass spectrometry, elemental analysis, and single‐crystal X‐ray crystallography. The synthesized compounds were screened for antiproliferative activity against four human cancer cell lines.Results and DiscussionCompound 5a exhibited the most potent antiproliferative profile, particularly against MCF‐7 breast cancer cells (IC50 = 34 nM), outperforming erlotinib (IC50 = 40 nM). Kinase inhibition assays further confirmed dual activity of 5a, with IC50 values of 87?nM and 33?nM against EGFR and HER‐2, respectively. Compound 5a induced apoptosis via activation of caspase‐3, ‐8, and ‐9, along with upregulation of Bax, downregulation of Bcl-2, and increased cytochrome c release. Flow cytometry analysis demonstrated that 5a caused significant G0/G1 phase arrest in MCF‐7 cells, indicating a cytostatic mechanism of action. Computational studies provided structural validation of the observed biological activities. Molecular docking studies showed a strong binding affinity 5a within the ATP‐binding pockets of EGFR and HER‐2, supported by key hydrogen bonding and hydrophobic interactions. These findings were further corroborated by 100 ns molecular dynamics simulations, which confirmed the structural stability and compactness of the 5a-HER-2 complex, as evidenced by low RMSD, consistent RMSF, and favorable radius of gyration and potential energy profiles. Additionally, ADME predictions revealed that 5a possesses favorable physicochemical and pharmacokinetic properties. Density Functional Theory (DFT) calculations provided insights into the electronic structure of 5a, highlighting favorable HOMO–LUMO distribution and electrostatic potential surfaces that support its dual‐binding behavior.